Correlation of DAPK1 methylation and the risk of gastrointestinal cancer: A systematic review and meta-analysis. - Wenzheng Yuan; Jinhuang Chen; Yan Shu; Sanguang Liu; Liang Wu; Jintong Ji; Zhengyi Liu; Qiang Tang; Zili Zhou; Yifeng Cheng; Bin Jiang; Xiaogang Shu (PLoS ONE)
Objective One of the critical mechanisms of gastrointestinal cancer pathogenesis is the silencing of death associated protein kinase 1 (DAPK1), which could be caused by aberrant methylation of the promoter. However, the relationship between DAPK1 methylation and the risk of gastrointestinal cancer is still controversial. Hence, we conducted this study to determine the potential correlation. Methods Eligible publications were searched in the Pubmed, Embase, and Cochrane Library through November 2016 according to the inclusion criteria and exclusion criteria. Revman 5.3 and Stata 12.0 software were used to analyze the relevant data regarding the association between the frequency of DAPK1 methylation and gastrointestinal cancer. Results A total of 22 studies with 2406 patients were included in this meta analysis. Methylation of DAPK1 was positively related with the risk of gastrointestinal cancer (odds ratio [OR] = 5.35, 95% confidence interval [CI]: 2.76-10.38, P<0.00001, random effects model). The source of heterogeneity was analyzed by sensitivity analysis and subgroup analysis. After omitting one heterogeneous study, the I2 decreased and the OR increased in pooled analysis. Also, the heterogeneity decreased most significantly in the subgroup of studies that had a sample size of less than 60 cases. Then, the correlations between DAPK1 methylation and clinicopathological features of gastrointestinal cancer were assessed. DAPK1 methylation was positively correlated with the lymph node (N) stage (positive vs. negative, OR = 1.45, 95%CI: 1.01-2.06, P = 0.04, fixed effects model) and poor differentiation (OR = 1.55, 95%CI: 1.02-2.35, P = 0.04, fixed effects model) in gastric cancer, and the association was significant among Asian patients. However, among cases of gastrointestinal cancer, the association between DAPK1 methylation and tumor (T) stage, N stage, distant metastasis (M) stage, and cancer differentiation were not statistically significant. Conclusions DAPK1 methylation is a potential biomarker for the early diagnosis of gastrointestinal cancer. Further analysis of the clinicopathological features indicated that aberrant methylation of DAPK1 is positively associated with the tumorigenesis of gastrointestinal cancer, and metastasis of gastric cancer.